A new species of Tomocerus (Collembola: Tomoceridae) from China - Ma, Yitong (Zootaxa, 2011)
Among the 15 extant genera of Tomoceridae, Tomocerus, with 73 species, is the largest. Most Tomocerus spp. have been described or reported from East Asia (Korea, Japan, China), 41 of them from China. Tomocerus spp. are large, active and epigaic, living in leaf litter. A new species, Tomocerus jilinensis sp. nov., is described from China here; setal variations of the ventral tube and blunt setae on hind foot of T. kinoshitai Yosii are also described. Both species were found on the Changbaishan Mountain, Jilin Province, China.